Calculation of Standardized Uptake Value (SUV) from PET-CT Image by Using In-House Developed MATLAB Software (Bangladesh Journal of Nuclear Medicine, 2022)
The Standardized Uptake Value (SUV) is one of the fundamental parameters to determine whether a region may be considered a “tumor” or “malignant” from PET-CT-derived images. When a measured SUV value is around 2.5, it is non-malignant. Again small tumorous areas can also show a maximum SUV of